Analisis Efektivitas Penggunaan QRIS terhadap Sistem Pembayaran Digital Mahasiswa dengan Business Intelligence - Hikmatun Hasana; Moch Luthfi Rachman; Shabrina Thufailah; Vannita Citra Kirana (Ikatan Ahli Informatika Indonesia, 2025)
This study aims to analyze the effectiveness of using the Quick Response Code Indonesian Standard (QRIS) as a digital payment system among university students through a Business Intelligence (BI) approach. The research employed a qualitative method with a single case study design within a campus environment, involving students, campus merchants, and institutional administrators. The findings reveal that perceived ease of use and perceived usefulness are the primary factors influencing students’ intention and intensity of using QRIS, while trust and security determine continued usage. Challenges identified include low digital financial literacy, limited internet infrastructure, and the persistence of cash transaction habits. The implementation of BI supports data-driven decision-making by identifying transaction patterns, failure rates, and user segmentation. This study highlights the importance of digital literacy enhancement, infrastructure support, and multi-stakeholder collaboration to improve the effectiveness of digital payment systems in higher education settings.